Physiological Basis of The Correction of Postural Disorders by Regular Ordered Muscular Activity - Shimanovskaya, Yanina Vasilievna (2020)
Posture deformation occurs under the influence of factors that violate the vertical position of the spine. When the load on the spine is redistributed, the position of the body is adjusted by selective training of the muscles of the trunk and changing the position of the pelvis in the frontal plane. Exercises for impaired posture should be aimed primarily at preventing progression and correcting curvature and twisting of the vertebrae. It is important not only the correction of curvature, but also the stabilization of the spine in a corrected position. Saving the achieved results contributes to the formation of a new static-dynamic stereotype of the spine. This is possible by deliberately influencing the upper and lower in relation to the main curvature of the links of the musculoskeletal system and muscle tone-regulating groups involved in posture formation.